Novel roles of intracrine angiotensin II and signalling mechanisms in kidney cells - Zhuo, Jia L (2007)
Angiotensin II (Ang II) has powerful sodium-retaining, growth-promoting and pro-inflammatory properties in addition to its physiological role in maintaining body salt and fluid balance and blood pressure homeostasis. Increased circulating and local tissue Ang II is one of the most important factors contributing to the development of sodium and fluid retention, hypertension and target organ damage. The importance of Ang II in the pathogenesis of hypertension and target organ injury is best demonstrated by the effectiveness of angiotensin-converting enzyme (ACE) inhibitors and AT(1)-receptor antagonists in treating hypertension and progressive renal disease including diabetic nephropathy. The detrimental effects of Ang II are mediated primarily by the AT(1)-receptor, while the AT(2)-receptor may oppose the AT(1)-receptor. The classical view of the AT(1)-receptor-mediated effects of Ang II is that the agonist binds its receptors at the cell surface, and following receptor phosphorylation, activates downstream signal transduction pathways and intracellular responses. However, evidence is emerging that binding of Ang II to its cell surface AT(1)-receptors also activates endocytotic (or internalisation) processes that promote trafficking of both the effector and the receptor into intracellular compartments. Whether internalised Ang II has important intracrine and signalling actions is not well understood. The purpose of this article is to review recent advances in Ang II research with focus on the mechanisms underlying high levels of intracellular Ang II in proximal tubule cells and the contribution of receptor-mediated endocytosis of extracellular Ang II. Further attention is devoted to the question whether intracellular and/or internalised Ang II plays a physiological role by activating cytoplasmic or nuclear receptors in proximal tubule cells. This information may aid future development of drugs to prevent and treat Ang II-induced target organ injury in cardiovascular and renal diseases by blocking intracellular and/or nuclear actions of Ang II.